ANALYSIS OF MARKETING AND PROMOTION STRATEGIES FOR INDIGENOUS TOURISM IN JHARKHAND USING SMITH’S 4HS FRAMEWORK: A SURVEY-BASED REVIEW - Kumar, Ravi; Chaturvedi, Mukesh (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Indigenous tourism presents a significant opportunity for socio-economic development while preserving cultural heritage. In Jharkhand, indigenous communities possess rich traditions, natural landscapes, and artistic assets that can be leveraged for sustainable tourism. However, effective marketing and promotional strategies are crucial to attract visitors, ensure long-term viability, and maximize community benefits. This study applies Smith’s 4Hs Framework—Habitat, Heritage, History, and Handicrafts—to analyze Jharkhand’s current indigenous tourism marketing strategies, identifying challenges and opportunities. The research integrates a systematic literature review, policy analysis, and comparative case studies to evaluate global best practices and their applicability to Jharkhand. Findings indicate that Jharkhand has immense indigenous tourism potential, but marketing limitations, poor digital presence, and infrastructural deficits hinder its growth. Successful indigenous tourism models from Northeast India, Rajasthan, Canada, and New Zealand highlight the importance of digital branding, community-driven storytelling, and sustainable business models. This study proposes strategic recommendations, including strengthening digital marketing, enhancing community participation, improving tourism infrastructure, and implementing sustainable tourism policies. By adopting these approaches, Jharkhand can establish itself as a leading indigenous tourism destination, ensuring economic empowerment for indigenous communities, environmental conservation, and global tourism engagement.